Thingking's Metaphorical Learning Model to Improve Reflective Thinking Skills in Mathematics - Jusmawati; Suradi Tahmir; Nurwati Djam'an (Cita konsultindo, 2025)
The ability of PGSD study program students in elementary school mathematics learning courses is still lacking, especially in reflective thinking skills. To overcome this, efforts are needed to improve students' reflective thinking skills; therefore, this article describes efforts to enhance reflective thinking skills with the metaphorical thinking learning model, learning that emphasizes students' activities to think metaphorically in finding an idea to link problems in questions with everyday experiences, metaphorical thinking is a model that bridges abstract concepts into more concrete things, Metaphorical thinking is a thinking process that uses metaphors to understand a metaphorical thinking concept called metaphorming, it is concluded that this study shows that the metaphorical thinking learning model improves reflective thinking skills in mathematics.